Influence of local reinforcement on the collision performance of B-pillar. Issue 1 (1st December 2022) - Li, F F; Tian, H B; Lin, J P
Abstract : The B-pillar is one critical structural component pertinent to automobile safety under side impact. Local reinforcement is an effective approach to enhance the energy absorption capability of the B-pillar without causing excessive deformation. In this paper, impact simulation of a B-pillar part was carried out with five different strength distribution schemes, including all low strength, all high strength, upper 1/3 reinforced, upper 2/3 reinforced, and rounded corners reinforced. The amount of deformation, the absorbed energy, and the stress distribution over the B-pillar were analyzed. It is observed that local reinforcement effectively reduced the deformation of B-pillar under impact while maintaining sufficient energy absorption ability.